PENGARUH KINERJA KEUANGAN DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI - Firmanda, Alfifa Ayu; Wahyuni, Nanik (Jurnal Riset Akuntansi Politala, 2024)
The purpose of this study was to determine the effect of financial performance and environmental performance on firm value and managerial ownership as a moderator between financial performance and environmental performance on firm value. This study uses a quantitative approach with a purposive sampling technique. The results showed that the EVA value was 0.8075> 0.05, the MVA value was 0.5351> 0.05, the environmental performance value was 0.0151 <0.05, and the KM value between EVA and firm value was 0.7839> 0.05. The KM value between MVA and firm value is 0.0095 < 0.05, while the KM value between environmental performance is 0.6758 > 0.05. Thus, EVA and MVA do not affect firm value, while environmental performance has a significant effect on firm value, and managerial ownership as a moderating variable does not moderate the effect of EVA, and environmental performance on firm value. However, managerial ownership can moderate the relationship between MVA and firm value.